The Relationship between World of Work Insights and Vocational Skills with Readiness to Enter the 21st Century World of Work in Electrical Power Installation Engineering Vocational Students in Jombang Regency - Rahman, Aiza; Irianto, Gunawan; Rahmawati, Yuni (LPPM Universitas Negeri Jakarta, 2025)
The objectives of this study are: (1) to describe the insights of the world of work owned by students of class XII (X1); (2) describe vocational skills mastered by students to get involved in the world of work in the 21st century (X2); (3) describe the readiness to enter the 21st century workforce as students as candidates for labor in the 21st century era (Y); (4) reveal the significance of the relationship between (X1) and (Y); (5) reveal the significance of the relationships (X2) and (Y); (6) revealing the significance of the simultaneous relationship between (X1) and (X2) with (Y); the 107 students of Department of Electrical Power Installation Engineering Program at vocational higj school regional Jombang. The data collection method is the questionnaire method. The questionnaire used has met the validity test and reliability test. Data analysis techniques used are partial correlation analysis and multiple regression, prerequisite test analysis, and analysis of relative-relative contributions. The regression equation Y = 30,215 + 0.035X1 + 0.481X2 with a significance of 0,000 indicates a positive and significant relationship between insight into the world of work and vocational skills with readiness to enter the 21st century work world.